Stability analysis andB ifurcation for an Bacterial Meningitis S preadingwith S tage S tructure : Mathematical M odeling - Abdulkadhim, Murtadha M.; Mohsen, Ahmed A.; Al Husseiny, Hassan F.; Hattaf, Khalid; Zeb, Anwar (Iraqi Journal of Science, 2024)
We introduce a mode l to describe the evolution of bacterial meningitis epidemics in a non constant population. We derive the value of the basic reproduction number of our model. We analy z e the local and global stability of the disease free and endemic equilibria. We confirm the results by a numerical analysis of the model.